Study of Magnetic Rotation in 193Pb: An Example of Collaboration Between Southeastern European Research Teams - Balabanski, D. L. (HNPS Advances in Nuclear Physics, 2020)
This paper summarizes the results of a series of experimental studies of magnetic rotation in mid-shell Pb nuclei. The focus is for the 29/2- v(1i^3/2)^{-1} (x) π(3s1/2)^{-2}(1h9/2)(i13/2) magnetic band in 193Pb, for which all experimental observables have been measured. This provides a stringent test of the theoretical models aiming at the description of such excitations. These studies have been carried out in col laboration with different research teams from the Balkans and are an example how to utilize most efficiently the huge scientific potential of the region.